2018
DOI: 10.3390/geosciences8060218
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sensitivity Analysis for Process Model Calibration of Natural Hazards

Abstract: Sensitivity analysis (SA) describes how varying inputs to a model subsequently varies its outputs. Its inclusion can support the systematic calibration of numerical models to back-calculate intensity properties of past torrent events that would otherwise be difficult or impossible to collect during their occurrence. Sensitivity analysis for model calibration is assessed with the back-calculation of a known torrent event. In particular, FLO-2D, a cell-based numerical model, is used to simulate the 2005 debris f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…The rheological parameters found in the literature [62] and the ones estimated by density curves from soil samples generated the opportunity to choose suitable rheological values in the model. However, Chow et al [4] considered that rheology calculated from soil samples generates much higher agreement in modeled results than the reported in the literature.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The rheological parameters found in the literature [62] and the ones estimated by density curves from soil samples generated the opportunity to choose suitable rheological values in the model. However, Chow et al [4] considered that rheology calculated from soil samples generates much higher agreement in modeled results than the reported in the literature.…”
Section: Discussionmentioning
confidence: 94%
“…The same behavior was found in HE simulations with a tendency to increase the flood area (8.28 ha), as shown in Figures 4i and 5i. In addition, the sensitivity analysis demonstrated that the Cv is the most important parameter for debris flow computation [4]. Therefore, debris mapping and real-time floodplain estimates would be utilized in the emergency management and flood alert systems to minimize risk using possible Cv based on historical estimations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum flood area and deposited volume are relatively easy to measures, and are probably the most used post-event measurements for calibrating debris flows models (Chow et al, 2018;Cesca and D'Agostino, 2008;D'Agostino and Tecca, 2006;Sosio et al, 2007;Frey et al, 2016;Quan Luna et al, 2011).…”
Section: Parameter Uncertainty Effectsmentioning
confidence: 99%
“…Boniello et al (2010) compared FLO-2D model results from a set of 12 back-calculated rheological parameters selected from previous studies, with another set of parameter values obtained from laboratory rheological analyses, finding a better representation of debris flow behavior with back-calculated parameters. Chow et al (2018) conducted simulations with FLO 2D using 26 different sets of rheological parameters obtained from previous studies, combined with different values of volumetric sediment concentration C v , specific gravity G s and the surface detention SD, a parameter used in FLO2D to represent flow detention. They found that the most important parameters were C v , SD and β 1 , which characterizes fluid viscosity.…”
Section: Introductionmentioning
confidence: 99%